2006
DOI: 10.2175/106143005x89571
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Techniques for the Detection of Helminth Ova in Drinking Water and Wastewater

Abstract: Many countries use wastewater for irrigation. The World Health Organization established, as reuse guidelines, a maximum value of 1 helminth ovum/L for irrigation. Various techniques for enumerating helminth ova in water have been published. To determine the most adequate method for Mexico, four techniques were compared: the U.S. Environmental Protection Agency (U.S. EPA), membrane‐filter, Leeds I, and Faust. Two types of water were used: drinking water and municipal wastewater effluent. Sensitivity, discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 7 publications
5
33
0
Order By: Relevance
“…The results indicated that the recovery rate of Method C was as high as 50% for treated wastewater and 12% for raw wastewater samples. This is comparable to a 26% recovery rate of Ascaris from treated wastewater reported by Maya et al, (2006), and 9-49% recovery rate of Cryptosporidium oocysts and Giardia cysts from environmental waters reported by Nieminski et al, (1995) using a similar methodology. One drawback of this method is the potential clogging of the sieve with large solid wastewater particles.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The results indicated that the recovery rate of Method C was as high as 50% for treated wastewater and 12% for raw wastewater samples. This is comparable to a 26% recovery rate of Ascaris from treated wastewater reported by Maya et al, (2006), and 9-49% recovery rate of Cryptosporidium oocysts and Giardia cysts from environmental waters reported by Nieminski et al, (1995) using a similar methodology. One drawback of this method is the potential clogging of the sieve with large solid wastewater particles.…”
Section: Discussionsupporting
confidence: 87%
“…Various methods have been used previously to recover hookworm ova from wastewater matrices with variable degrees of success (Bowman et al, 2003;McCuin and Clancy, 2005;Maya et al, 2006;Ensink et al, 2008). In light of this, several rapid concentration methods for the recovery of hookworm ova from wastewater matrices including sludge samples were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations